A Highly Contiguous Reference Genome for Northern Bobwhite (Colinus virginianus). Issue 12 (1st December 2019) - Salter, Jessie F; Johnson, Oscar; Stafford, Norman J; Herrin, William F; Schilling, Darren; Cedotal, Cody; Brumfield, Robb T; Faircloth, Brant C
Abstract: Northern bobwhites ( Colinus virginianus ) are small quails in the New World Quail family (Odontophoridae) and are one of the most phenotypically diverse avian species. Despite extensive research on bobwhite ecology, genomic studies investigating the evolution of phenotypic diversity in this species are lacking. Here, we present a new, highly contiguous assembly for bobwhites using tissue samples from a vouchered, wild, female bird collected in Louisiana. By performing a de novo assembly and scaffolding the assembly with Dovetail Chicago and HiC libraries and the HiRise pipeline, we produced an 866.8 Mb assembly including 1, 512 scaffolds with a scaffold N50 of 66.8 Mb, a scaffold L90 of 17, and a BUSCO completeness score of 90.8%. This new assembly represents approximately 96% of the non-repetitive and 84% of the entire bobwhite genome size, greatly improves scaffold lengths and contiguity compared to an existing draft bobwhite genome, and provides an important tool for future studies of evolutionary and functional genomics in bobwhites.